PECTORALIS FLAP REPAIR OF DEFECT IN THE SURGICAL TREATMENT OF LOCALLY ADVANCED AND RECURRENT OROPHARYNGEAL CANCER - D. V. Sikorsky; S. O. Podvyaznikov; A. N. Volodin; A. A. Chernyavsky; N. A. Lavrov; S. V. Penin (Опухоли головы и шеи)
The paper details the surgical features of pectoralis flap repair of defect in in the treatment of locally advancedand recurrent oropharyngeal cancer.